Resistance to vertical root fracture of root filled teeth using different conceptual approaches to canal preparation. (3rd October 2015) - Prado, M.; de Lima, N. R. B.; de Lima, C. O.; Gusman, H.; Simão, R. A.
Abstract: Aim: To evaluate the resistance to vertical root fracture of root filled teeth using different root canal preparation concepts: apical stop and continuously tapering preparation, with different foraminal enlargement. In addition, the effect of filling associated with these different concepts was assessed. Methodology: Ninety single‐rooted premolars were used. The crowns were removed to standardize the root length at 11 mm. Ten roots were not instrumented and not filled (control group). The other roots were divided into four groups ( n  = 20): apical stop to finishing file size 25, 0.08 taper; apical stop to finishing file size 45, 0.02 taper; continuously tapering preparation to finishing file size 25, 0.08 taper; and continuously tapering preparation to finishing file size 45, 0.02 taper. Afterwards, 10 roots of each group were root filled using Gutta‐percha and AH Plus. A continuous wave of condensation was used as the filling technique. The roots were evaluated as regards resistance to vertical fracture using a universal testing machine. The data were evaluated using the Kruskal–Wallis and Mann–Whitney tests. Results: No significant difference in performance was observed between continuously tapering preparation size 25, 0.08 taper and apical stop size 45, 0.02 taper groups. Lower resistance values were found in continuously tapering preparation size 45, 0.02 taper group and the highest in apical stop size 25, 0.08 taper group. After filling, a significant increase in resistance values was observed in all groups. In addition, the continuously tapering preparation size 45, 0.02 taper group had values comparable with those of the control. Conclusion: The different canal preparation techniques reduced resistance to fracture when compared with the control group; however, after root filling, there was a significant increase in resistance.